Point‐of‐Care Ultrasonography Detects Vanishing Air Embolism Following Central Venous Catheter Removal in a Patient With Chest Tube Drainage: A Case Report - Yong Chae Jung; Min‐Woong Kang; Hyun Jin Cho; Yooyoung Chong; Jun Wan Lee (Clinical Case Reports)
ABSTRACT Air embolism from central venous access removal may be fatal, even when removed in the supine position. This case demonstrates that a high index of suspicion combined with point‐of‐care ultrasonography is vital for the rapid diagnosis and management of this condition.